Multiple Myeloma-Derived Exosomes Regulate the Functions of Mesenchymal Stem Cells Partially via Modulating miR-21 and miR-146a - Qian Cheng; Xin Li; Jingru Liu; Qinmao Ye; Yanfang Chen; Sanqin Tan; Jing Liu (Stem Cells International)
Exosomes derived from cancer cells can affect various functions of mesenchymal stem cells (MSCs) via conveying microRNAs (miRs). miR-21 and miR-146a have been demonstrated to regulate MSC proliferation and transformation. Interleukin-6 (IL-6) secreted from transformed MSCs in turn favors the survival of multiple myeloma (MM) cells. However, the effects of MM exosomes on MSC functions remain largely unclear. In this study, we investigated the effects of OPM2 (a MM cell line) exosomes (OPM2-exo) on regulating the proliferation, cancer-associated fibroblast (CAF) transformation, and IL-6 secretion of MSCs and determined the role of miR-21 and miR-146a in these effects. We found that OPM2-exo harbored high levels of miR-21 and miR-146a and that OPM2-exo coculture significantly increased MSC proliferation with upregulation of miR-21 and miR-146a. Moreover, OPM2-exo induced CAF transformation of MSCs, which was evidenced by increased fibroblast-activated protein (FAP), α-smooth muscle actin (α-SMA), and stromal-derived factor 1 (SDF-1) expressions and IL-6 secretion. Inhibition of miR-21 or miR-146a reduced these effects of OPM2-exo on MSCs. In conclusion, MM could promote the proliferation, CAF transformation, and IL-6 secretion of MSCs partially through regulating miR21 and miR146a.